Inconclusive benefit of adjuvant 90Yttrium hydroxyapatite to radiosynovectomy for diffuse-type tenosynovial giant-cell tumour of the knee. (July 2018) - Gortzak, Y.; Vitenberg, M.; Frenkel Rutenberg, T.; Kollender, Y.; Dadia, S.; Sternheim, A.; Morag, G.; Farkash, U.; Rath, E.; Kramer, M.; Drexler, M.
Abstract : Aims: Intra-articular 90 Yttrium ( 90 Y) is an adjunct to surgical treatment by synovectomy for patients with diffuse-type tenosynovial giant-cell tumour (dtTGCT) of the knee, with variable success rates. Clinical information is, however, sparse and its value remains unclear. We investigated the long-term outcome of patients who underwent synovectomy with and without adjuvant treatment with 90 Yttrium. Patients and Methods: All patients with dtTGCT of the knee who underwent synovectomy between 1991 and 2014 were included in the study. Group A patients underwent synovectomy and an intra-articular injection of 90 Yttrium between six and eight weeks after surgery. Group B patients underwent surgery alone. Results: There were 34 patients in group A and 22 in group B. Recurrence of dtTGCT was identified by MRI, which was undertaken in patients with further symptoms. At a mean follow-up of 7.3 years (2.5 to 25.4), there was residual disease in 15 patients in group A and 11 in group B (p < 0.363). The mean Musculoskeletal Tumor Society (MSTS) score at final follow-up was 85% and 83%, respectively (p < 0.91). Conclusion: There were no significant differences in outcome between patients treated surgically for dtTGCT of the knee with or without an adjuvant intra-articular injection of 90 Yttrium. We were unable to provide conclusive evidence of any benefits derived from the adjuvant treatment. Cite this article: Bone Joint J 2018;100-B:984–8.